PERLUASAN DARI RING REGULAR - Devi Anastasia Shinta; YD Sumanto (MATEMATIKA FSM, UNDIP, 2013)
Regular ring R is a nonempty set with two binary operations that satisfied ring axioms and qualifies for any x in R there is y in R such that x=xyx. Regular ring R ̃ is a ring of the set of endomorphism R^+ with identity. For any regular ring R and R' can be defined a bijective mapping from R to R' that satisfies ring homomorphism axioms or in the otherwords that mapping is an isomorphism from R to R'. By using the concept of regular ring and ring isomorphism can be determined extension of regular ring. Regular ring R is said to be embedded in regular ring R^R ̃ if there exists a subring R^0 of R^R ̃ such that R is isomorphic to R^0. Furthermore, regular ring R^R ̃ can be said as an extension of regular ring R.